The identification of new triterpenoids in eucalyptus globulus wood - Lourenço, Ana (2021)
Eight polyhydroxy triterpenoid acids, hederagenin, (4α)-23-hydroxybetulinic acid, maslinic acid, corosolic acid, arjunolic acid, asiatic acid, caulophyllogenin, and madecassic acid, with 2, 3, and 4 hydroxyl substituents, were identified and quantified in the dichloromethane extract of Eucalyptus globulus wood by comparing their GC-retention time and mass spectra with standards. Two other triterpenoid acids were tentatively identified by analyzing their mass spectra, as (2α)-2- hydroxybetulinic acid and (2α,4α)-2,23-dihydroxybetulinic acid, with 2 and 3 hydroxyl substituents. Two MS detectors were used, a quadrupole ion trap (QIT) and a quadrupole mass filter (QMF). The EI fragmentation pattern of the trimethylsilylated polyhydroxy structures of these triterpenoid acids is characterized by the sequential loss of the trimethylsilylated hydroxyl groups, most of them by the retro-Diels-Alder (rDA) opening of the C ring with a π-bond at C12-C13. The rDA C-ring opening produces ions at m/z 320 (or 318) and m/z 278 (or 277, 276, 366). Sequential losses of the hydroxyl groups produce ions with m/z from [M - 90] to [M - 90*y], where y is the number of hydroxyl substituents present (from 2 to 4). Moreover, specific cleavage in ring E was observed, passing from m/z 203 to m/z 133 and conducting other major fragments such as m/z 189.